Antibacterial activity of plasma from crocodile (Crocodylus siamensis) against pathogenic bacteria - Kommanee Jintana; Preecharram Sutthidech; Daduang Sakda; Temsiripong Yosapong; Dhiravisit Apisak; Yamada Yuzo; Thammasirirak Sompong (BMC, 2012)
Abstract Background The Siamese crocodile (Crocodylus siamensis) is a critically endangered species of freshwater crocodiles. Crocodilians live with opportunistic bacterial infection but normally suffer no adverse effects. They are not totally immune to microbial infection, but their resistance thereto is remarkably effective. In this study, crude and purified plasma extracted from the Siamese crocodile were examined for antibacterial activity against clinically isolated, human pathogenic bacterial strains and the related reference strains. Methods Crude plasma was prepared from whole blood of the Siamese crocodile by differential sedimentation. The crude plasma was examined for antibacterial activity by the liquid growth inhibition assay. The scanning electron microscopy was performed to confirm the effect of crude crocodile plasma on the cells of Salmonella typhi ATCC 11778. Effect of crude crocodile plasma on cell viability was tested by MTT assay. In addition, the plasma was purified by anion exchange column chromatography with DEAE-Toyopearl 650 M and the purified plasma was tested for antibacterial activity. Results Crude plasma was prepared from whole blood of the Siamese crocodile and exhibited substantial antibacterial activities of more than 40% growth inhibition against the six reference strains of Staphylococcus aureus, Salmonella typhi, Escherichia coli, Vibrio cholerae, Pseudomonas aeruginosa, and Staphylococcus epidermidis, and the four clinical isolates of Staphylococcus epidermidis, Pseudomonas aeruginosa, Salmonella typhi, and Vibrio cholerae. Especially, more than 80% growth inhibition was found in the reference strains of Salmonella typhi, Vibrio cholerae, and Staphylococcus epidermidis and in the clinical isolates of Salmonella typhi and Vibrio cholerae. The effect of the crude plasma on bacterial cells of Salmonella typhi, a certain antibacterial material probably penetrates progressively into the cytoplasmic space, perturbing and damaging bacterial membranes. The effect of the crude plasma was not toxic by the yellow tetrazolium bromide (MTT) assay using a macrophage-like cell, RAW 264.7. The pooled four fractions, designated as fractions D1-D4, were obtained by column chromatography, and only fraction D1 showed growth inhibition in the reference strains and the clinical, human pathogenic isolates. Conclusions The crude and purified plasma from the Siamese crocodile significantly showed antibacterial activity against pathogenic bacteria and reference strains by damage cell membrane of target bacterial cells. From the MTT assay, the Siamese crocodile plasma was not cytotoxic to the cells.